Individual differences in the link between perception and production and the mechanisms of phonetic imitation. Issue 6 (3rd July 2019) - Kim, Donghyun; Clayards, Meghan
ABSTRACT: This study investigates the relationship between speech perception and production using explicit phonetic imitation. We used manipulated natural vowel ( head-had ) stimuli varying in spectral quality and duration in both perception and production tasks to explore the perception-production link in a direct and controlled way. We examined (1) whether individual listeners' perceptual cue weights are related to their patterns of phonetic imitation and (2) phonological and perceptual constraints underlying phonetic imitation. Results showed that better perceptual abilities (i.e. larger cue weights) were related to better imitation of vowel duration. Furthermore, imitation of vowel spectral quality was mediated by contrast maintenance while vowel duration was not. Overall, vowel duration was better imitated despite being the less important cue perceptually. These results suggest that speech perception and production are indeed linked at the individual level, and both linguistic and perceptual-cognitive factors play a role in this process.